2016
DOI: 10.4102/ajlm.v5i1.280
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the World Health Organization Regional Office for Africa Stepwise Laboratory Quality Improvement Process Towards Accreditation

Abstract: BackgroundThe increase in disease burden has continued to weigh upon health systems in Africa. The role of the laboratory has become increasingly critical in the improvement of health for diagnosis, management and treatment of diseases. In response, the World Health Organization Regional Office for Africa (WHO AFRO) and its partners created the WHO AFRO Stepwise Laboratory (Quality) Improvement Process Towards Accreditation (SLIPTA) program.SLIPTA implementation processWHO AFRO defined a governance structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…The scale-up of VL testing and EID has led to the decentralization of molecular laboratories in order to meet country needs (220). These laboratories are encouraged to participate in strengthening laboratory management toward accreditation to improve laboratories and then be enrolled into the WHO/Stepwise Laboratory Quality Improvement Process towards Accreditation for formal recognition using the 5-star grading system (304)(305)(306). Furthermore, some laboratories are aiming for international ISO15189 accreditation and ensuring compliance to standards in the laboratory (307,308).…”
Section: Ensuring and Monitoring Quality Of Molecular Testing In Rlsmentioning
confidence: 99%
“…The scale-up of VL testing and EID has led to the decentralization of molecular laboratories in order to meet country needs (220). These laboratories are encouraged to participate in strengthening laboratory management toward accreditation to improve laboratories and then be enrolled into the WHO/Stepwise Laboratory Quality Improvement Process towards Accreditation for formal recognition using the 5-star grading system (304)(305)(306). Furthermore, some laboratories are aiming for international ISO15189 accreditation and ensuring compliance to standards in the laboratory (307,308).…”
Section: Ensuring and Monitoring Quality Of Molecular Testing In Rlsmentioning
confidence: 99%
“…In addition to the quality improvement registered between baseline and exit audits, laboratories are recommended to continuously apply laboratory quality systems to achieve international accreditation. 27 To be eligible for international accreditation, a laboratory in the SLMTA program is required to score 95% or more out of 275 points on the SLIPTA checklist audit. 22 , 28 This score is equivalent to five stars on the WHO grading scale of 0 (<55%) to five stars (≥95%), and the awarded score in this WHO system is valid for 2 years.…”
mentioning
confidence: 99%
“…Predisposition to the observed low quality is neither well studied nor understood; however, as earlier studies indicated, laboratory size and staff training may be some of the determinants [ 14 , 16 ]. Although we did not study the effect of staffing and their training, the observed low scores for these laboratories concedes the fact that medical laboratory training may not suffice, but rather it ought to be augmented with more comprehensive quality management systems as earlier reported [ 11 , 17 ]. Additionally, as the research laboratory scored the lowest acceptable accreditation level, it had clinical trials at the time of this survey, suggesting that this may have set certain quality needs.…”
Section: Discussionmentioning
confidence: 89%
“…SLIPTA is a framework for improving quality of public health laboratories in developing countries to achieve the requirements of the ISO 15189 standard [ 6 ]. The WHO AFRO SLIPTA program has been recommended for low resource set up [ 11 ]. The SLIPTA checklist is based on collection of patient samples, interpretation of test results, acceptable turnaround times, testing in medical emergency, routine internal quality control (IQC) and an 80%, 2-cycle pass rate on external quality control (EQC).…”
Section: Introductionmentioning
confidence: 99%